Reorganizing the Structure of Indian School Science Education with reference to Committees and Commissions - Dash, Sagnika; Bhoi, Chandrasekhar (International Journal of Multidisciplinary Approach Research and Science, 2024)
National Policy on Education reiterated the integration of India’s culture and heritage with scientific thinking and scientific discoveries. Imparting formal education has enormously changed over the years in India with integration of science education in the curriculum and emergence of the idea of digitalization of education. Scientific progress brings about amelioration of individual and social development. For scientific progress to occur, not only the science research centres should be expanded and developed but fundamentally the schools, colleges and universities imparting science education must be strengthened in quality. This article discusses in retrospect, about the referring to the recommendations of various committees and commissions of pre and post independence period, in attempt to provide a comprehensive picture of development of a holistic education system in India .